Pengaruh Ukuran Perusahaan, Profitabilitas, dan Leverage terhadap Audit Report Lag - Thomasna Illahi; Oknaryana Oknaryana (Universitas Negeri Padang, 2023)
This study to determine the effect between company size, profitability, leverage, and audit report lag (ARL) on the Property and Real Estate sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period. This study uses panel data regression analysis and sampling in this study using purposive sampling method. Based on the predetermined purposive sampling criteria, there are 45 companies in the property and real estate sector that can be sampled. Firm size is measured by total assets, profitability is represented by return on assets (ROA), and leverage is measured by debt-to-assets ratio. The results of the study reveal evidence of a relationship between firm size, profitability, leverage and ARL. First, firm size shows no significant negative correlation with ARL. Second, profitability shows a significant negative relationship with ARL, indicating that firms with higher profitability tend to have more efficient financial reporting procedures, resulting in shorter audit report lag. Finally, leverage shows a significant positive relationship with ARL, which suggests that companies with higher debt-to-asset ratios may experience longer reporting delays due to increased financial risk.